Comparison of Cardiovascular Health Between US Army and Civilians. Issue 12 (18th June 2019) - Shrestha, Alice; Ho, Tiffany E.; Vie, Loryana L.; Labarthe, Darwin R.; Scheier, Lawrence M.; Lester, Paul B.; Seligman, Martin E. P.
Abstract : Background: Cardiovascular conditions are common in US Army and civilian populations. The recently developed concept of ideal cardiovascular health provides a new approach to evaluating population cardiovascular status. Methods and Results: We defined a cohort of 263 430 active duty Army personnel, aged 17 to 64 years, who completed a 2012 physical examination and a corresponding subset of the noninstitutionalized, civilian US population, who participated in the National Health and Nutrition Examination Survey (NHANES) 2011 to 2012 cycle. We compared 4 cardiovascular health metrics (current smoking, body mass index, blood pressure, and diabetic status) between Army and civilian groups overall, and separately by sex, race/ethnicity, and age. The Army population was younger, was less often women or Hispanic, and had less post–high school education than the NHANES population. Smoking rates were ≈20% in the Army and NHANES groups, but <15% among Army women and Hispanics. Overall, one third of the Army and NHANES groups and NHANES women, but nearly half of Army women, demonstrated ideal body mass index. Ideal blood pressure was strikingly less prevalent in the Army than NHANES participants (30% versus 55%). Diabetes mellitus was rare in both groups. Conclusions: Ideal cardiovascular health was less prevalent in the Army than NHANES group, despite exclusion of the least healthy recruits. Prevalence of ideal body mass index and blood pressure was low in both the Army and NHANES groups, even at early adult ages. This finding reveals the need for policy changes to promote, preserve, and improve ideal cardiovascular health in both the Army and the US population as a whole.